Pengaruh Investasi, EBITDA, dan Nilai Pasar Saham Perusahaan terhadap Audit Fee pada Sektor Perbankan Swasta di Bursa Efek Indonesia (BEI) - Ricky Bryan D.P. Tampubolon; Arya Prana Purba; Akbar Anggisa; Siti Nur Annida; Khairunnisa, Firda (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to analyze the impact of investment, EBITDA, and company market value on audit fee in the private banking sector listed on the Indonesia Stock Exchange. The research is motivated by substantial variations in audit fees among companies and the crucial role of financial characteristics in audit fee determination. A quantitative approach is employed, utilizing secondary data from annual reports of private banks for the period 2022-2024, and multiple linear regression analysis is used to examine the relationships between independent variables and audit fee. Findings from descriptive, validity, and reliability tests indicate that the primary data meet the basic requirements for analysis, although instrument consistency is relatively low. Main regression analysis reveals that investment has a significant and positive effect on audit fee, while EBITDA and market value show no significant impact. Simultaneously, the three independent variables demonstrate a strong predictive ability for audit fee. The implication of this research encourages management and auditors to prioritize investment factor in audit fee negotiations while promoting better measurement instruments for future research.